Star Wars : Episode II : Attack of the Clones - Daniels, Anthony; Baker, Kenny; 1934-; Oz, Frank; Burtt, Ben.; 1922-; Williams, John; 1932-; Bocquet, Gavin; Biggar, Trisha; Tattersall, David; Lee, Christopher; et al. (Beverly Hills, Calif., 2002)
Ten years after the events of Phantom menace, Senator Padme Amidala survives an assassination attempt as she returns to Coruscant for an important vote. The Jedi Council send Obi-Wan Kenobi and Annikin Skywalker to protect her. After tracking the assassin, Obi-Wan is sent to Kamino to continue their investigations while Annikin is sent with Amidala to Naboo. While Annikin and Amidala are falling in love on Naboo, Obi-Wan is investigating the connection between the assassination attempt and a growing sepeartist movement, which could bring the Republic to the brink of civil war.
Keywords: Feature films; Video recordings for the hearing impaired; Star Wars films; Science fiction films